Little Penguin's new friend - Driscoll, Laura; Bentley, Tadgh (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2019)
After his friends' reports about bears, Little Penguin is anxious about a new polar bear friend's visit.
Keywords: Penguins -- Fiction; Polar bear -- Fiction; Bears -- Fiction; Friendship -- Fiction